Tinjauan Video Animasi Berjudul â€œLagu Anak Islami - 25 Nabiâ€ Karya Muffin Graphics Menggunakan Analisis Semiotika Saussure - Ul Haq, Edo Gavinda; Kurniawan, Ivan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
Animation is an audio visual media that aims to provide information on public spaces. Good animation certainly has content, images, and visual elements that support it so that the message delivered will be easily understood by the audience. Animation is also often used as a medium of education in early childhood, one of which is religious education. The company that makes animations in religious education in children is Muffin Graphics with one of its works, an animated video entitled "Islamic Children's Songs - 25 Prophets" with a character named Annisa. However, in the video there are some interesting visuals to study, such as the existence of objects that resemble pyramids, boats in the sandy background, and so on. With the visuals in the video clip, it is interesting to study more deeply. This study aims to determine the visual message used in the video. The method used in this research is observation by downloading the video, chopping each scene according to the setting of the place, and finding a valid source with Saussure's semiotic theory. Presentation of writing will be done with narrative or descriptive analysis.